Cognition Enhancing Potential of Aqueous Leaf Extract of in Mice - Daisy Jepkosgei Kipkemoi Msc; Anthony Murithi Ireri PhD; Mathew Piero Ngugi PhD (Journal of Evidence-Based Integrative Medicine, 2023)
Amaranthus dubius is a vegetable consumed for its nutritional content in Kenya. In herbal medicine, A. dubius is utilized to relief fever, anemia and hemorrhage. Additionally, it is utilized to manage cognitive dysfunction and is considered to augment brain function, but there is no empirical evidence to support this claim. The contemporary study investigated cognitive enhancing potential of A. dubius in mice model of Alzheimer's disease (AD)-like dementia induced with ketamine . Cognitively damaged mice were treated with aqueous extract of A. dubius leaf upon which passive avoidance task (PAT) was used to assess the cognitive performance. At the end of passive avoidance test, brains of the mice were dissected to evaluate the possibility of the extract to inhibit hallmarks that propagate AD namely oxidative stress and acetylcholinesterase activity. Additionally, characterization of secondary metabolites was done using liquid chromatograph- mass spectrometry analysis. During PAT test, extract-treated mice showed significantly increased step-through latencies than AD mice, depicting ability of A. dubius to reverse ketamine-induced cognitive decline. Further, the extract remarkably lowered malondialdehyde levels to normal levels and effectively inhibited acetylcholinesterase enzyme. The study showed that A. dubius extract is endowed with phytoconstituents that possess anti-oxidant and anticholinesterase activities. Thus, this study confirmed promising therapeutic effects of 200, 300 and 400 mg/kg bw of A. dubius extract with potential to alleviate cognitive disarray observed in AD.